Hydrogen storage properties of nanocrystalline and amorphous Pr–Mg–Ni-based alloys synthesized by mechanical milling. (31st August 2017) - Zhang, Yanghuan; Li, Yaqin; Shang, Hongwei; Yuan, Zeming; Cai, Ying; Qi, Yan; Zhao, Dongliang
Abstract: To improve the hydrogen storage properties of PrMg12 alloy, one Mg atom was replaced by one Ni atom in the alloy. And then the PrMg11 Ni alloy was milled with two or three times Ni powers. The as-milled PrMg11 Ni + x wt.% Ni ( x = 0, 100, 200) (PrMg11 Ni- x Ni ( x = 0, 100, 200)) alloys possess a nanocrystalline and amorphous structure. The gaseous hydrogen storage properties were tested by Sievert apparatus and Differential scanning calorimetry (DSC) connected with a H2 detector. The results indicate that increasing Ni content have obvious improvement effects on the gaseous hydrogen storage kinetics and thermodynamics for both the hydrogenation and dehydrogenation reaction. Furthermore, the variation of milling time also has an obvious influence on gaseous hydrogen storage properties of the alloys. The hydrogen storage capacity firstly increases and decreases again with prolonging milling time, and the peak values are 5.859 wt.% for the x = 100 alloy and 6.164 wt.% for the x = 200 alloy. The hydrogen absorption rates have similar trends, but the hydrogen desorption rates always increase. The hydrogen desorption activation energy markedly lowers with Ni content and milling time increasing, which is the real reason for the improvement of hydrogen desorption kinetics. Highlights: An Mg atom in PrMg12 -type alloys was replaced by a Ni atom. The PrMg11 Ni- x Ni alloys possess the nanocrystalline and amorphous structure. Prolonging milling time has an obvious influence on hydrogen storage properties. Increasing Ni content improve the kinetics and thermodynamics. Activation energy was calculated by Arrhenius and Kissinger methods.